PERANCANGAN SISTEM INFORMASI AKUNTANSI METODE SINGLE STEP UNTUK MENGHITUNG LABA RUGI STUDI KASUS PADA CHAMPION GYM CIREBON - Suwandi, Suwandi; Asfi, Marsani; Firlisia, Viona; Chandra, Sylvia (Universitas Medan Area, 2019)
This study discuss the problems in Champion Gym that are related to accounting records is the calculation of the income statement still using manual methods, not using a computerized system that complies with accounting standards. So that makes it difficult for management in terms of calculating the income statement every month. The purpose of this study was to create a Profit and Loss Report Calculation System Application Using Single Step Method, which is expected to help Champion Gym management in calculating the company's profit / loss for each period .. The profit and loss calculation application using the Single Step Method can facilitate the management of Champion Gym in calculate income, costs and profit / loss generated each period. So that Champion Gym management can find out in real terms about the company's profit / loss every accounting period. The results of this system are expected to have an impact on the efficiency and effectiveness of Gym operations and obtain an accurate income statement through maximum profit.